Successful societies: Decision‐making and the quality of attentiveness. (27th December 2019) - Stones, Rob; Turner, Bryan S.
Abstract: Combining moral philosophy with sociological theory to build on themes introduced in Hall and Lamont's Successful Societies (2009), the paper outlines a distinctive perspective. It holds that a necessary condition of successful societies is that decision‐makers base their decisions on a high level of attentiveness (concern and comprehension) towards subjectively valued and morally legitimate forms of life. Late modern societies consist of a plurality of forms of life, each providing grounds for what Alasdair MacIntyre has called internal goods —valued and morally valuable practices. The status of such goods is examined, and distinctions are drawn between their manifest and latent, and transposable and situationally specific, characteristics. We integrate this refined idea of internal goods into a developed conception of habitus that is both morally informed and situationally embedded. The sociological approach of strong structuration theory (SST) is employed to demonstrate how this conception of habitus can guide the critique of decision‐making that damages internal goods. We identify the most pervasive and invidious forms of damaging decision‐making in contemporary societies as those involving excessive forms of instrumental reasoning . We argue that our developed conception of habitus, anchored in the collectively valued practices of specific worlds, can be a powerful focus for resistance. Accounts of scholarship in higher education and of the white working class in America illustrate the specificities of singular, particular, social worlds and illuminate critical challenges raised by the perspective we advocate.